A Staphylococcus aureus Regulatory System that Responds to Host Heme and Modulates Virulence - Torres, V; Stauff, D; Pishchany, G; Bezbradica, J; Gordy, L; Iturregui, J; Anderson, K; Dunman, P; Joyce, S; Skaar, E (Cell Press, 2007)
Staphylococcus aureus, a bacterium responsible for tremendous morbidity and mortality, exists as a harmless commensal in approximately 25% of humans. Identifying the molecular machinery activated upon infection is central to understanding staphylococcal pathogenesis. We describe the heme sensor system (HssRS) that responds to heme exposure and activates expression of the heme-regulated transporter (HrtAB). Inactivation of the Hss or Hrt systems leads to increased virulence in a vertebrate infection model, a phenotype that is associated with an inhibited innate immune response. We suggest that the coordinated activity of Hss and Hrt allows S. aureus to sense internal host tissues, resulting in tempered virulence to avoid excessive host tissue damage. Further, genomic analyses have identified orthologous Hss and Hrt systems in Bacillus anthracis, Listeria monocytogenes, and Enterococcus faecalis, suggesting a conserved regulatory system by which Gram-positive pathogens sense heme as a molecular marker of internal host tissue and modulate virulence.